THE WATER PURIFICATION SYSTEM OF MACHINE-BUILDING COMPLEX FROM OIL-PRODUCTS - A. S. Panasugin; I. A. Silvanovich; D. P. Mihalap; D. B. Nemenenok (Литьë и металлургия, 2005)
The developed system of purification of sewage water from petroleum products allows to provide efficiency of purification up to the norms of PDK, and if necessary the devices can be used as a separate modules or their combinations.